2011
DOI: 10.1007/s11010-011-0842-1
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin promotes odontoblast-like MDPC-23 cell differentiation via activation of ERK1/2 and p38 MAPK

Abstract: Amelogenin (AMG) is a highly conserved protein secreted by ameloblasts. Some research indicates that AMG might induce the differentiation and maturation of odontoblasts. The aim of this study was to clarify the function of AMG during the differentiation of odontoblast-like MDPC-23 cells. The results revealed that the alkaline phosphatase activity and the number of mineralized nodules were significantly enhanced in AMG-overexpressing MDPC-23 cells during the mineralization process. Tissue-specific markers such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The roles of FGFR/MEK/Erk1/2 signaling in odontoblast differentiation and the crosstalk between the FGF/FGFR and BMP/BMPR signaling pathways in the stimulatory effects of FGF2 on odontoblast differentiation in our study are consistent with previously reported roles of these pathways in osteoblasts (Fakhry et al 2005;Spector et al 2005;Ye et al 2006;Yao et al 2011;Marie 2012;Marie et al 2012;Zhang et al 2012;Zhao et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The roles of FGFR/MEK/Erk1/2 signaling in odontoblast differentiation and the crosstalk between the FGF/FGFR and BMP/BMPR signaling pathways in the stimulatory effects of FGF2 on odontoblast differentiation in our study are consistent with previously reported roles of these pathways in osteoblasts (Fakhry et al 2005;Spector et al 2005;Ye et al 2006;Yao et al 2011;Marie 2012;Marie et al 2012;Zhang et al 2012;Zhao et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that several compounds, such as sodium fluoride (NaF) [27], amelogenin [28], or lipopolysaccharide (LPS) [29], can activate the ERK1/2 signaling pathway in MDPC-23 cells. The activation of the ERK1/2 signaling pathway was found to be crucial for regulating p35 expression [1416,30], and it has also been reported that TGF-β1 can activate non-Smad signaling pathways such as the ERK1/2 pathway [31].…”
Section: Resultsmentioning
confidence: 99%
“…Enamel matrix derivatives have been studied extensively both in vitro and in vivo. Amelogenin has been shown to stimulate osteoblast differentiation (Olivares-Navarrete et al, 2013) and to increase the mitogen activated protein kinase (MAPK) extracellular signal-regulated kinase (ERK1/2) (Yao et al, 2011), implicating this signaling cascade in its mechanism of action. However, the specific roles of other components of these extracts on cell response are not well understood.…”
Section: Introductionmentioning
confidence: 99%